An Anesthesia Attempt to Be Green: How Do You Waste Your Carbon Dioxide Absorbers?. Issue 11 (1st December 2019) - Burbridge, Mark A.; Chua, Pandora; Jaffe, Richard A.; Pearl, Ronald G.; Brock-Utne, John G.
Abstract : Operating room waste is categorized as noncontaminated solid waste (SW) and regulated medical waste (RMW). RMW is treated by autoclaving at an increased economic and environmental cost. We evaluated these costs with a focus on the disposable carbon dioxide (CO2 ) absorbers. At our institution, exhausted CO2 absorbers were discarded as RMW. We collaborated with product representatives, anesthesia and perioperative staff, and waste management personnel to identify opportunities and barriers for recycling and waste reduction. Ultimately, we agreed to discard CO2 absorbers as SW instead of RMW, a strategy that is practical, less expensive, and more environmentally appropriate.